Nutritional Status of Schizophrenic Patients Attending Outpatient Department of Psychiatry in Dr.Hasan Sadikin Hospital - Maisyarah, Tiara Aulia; Nugraha, Gaga Irawan; Lidyana, Lynna (Althea Medical Journa, 2014)
Background: Currently, schizophrenia is associated with many health problems due to weight changes caused by lifestyle changes and consumption of antipsychotic drugs (APDs). Nutritional status assessment is needed in order to lower the comorbidity through early detection of risk factors.Methods: This descriptive cross-sectional study involved 94 schizophrenic patients selected using consecutive sampling in October 2012 in Psychiatry Outpatient Department, Dr. Hasan Sadikin General Hospital, Bandung. An anthropometric measurement was verified (body mass index and waist circumference), physical activity level, type of antipsychotic drugs (APDs) used and duration of treatment acquired from medical records. Results: Among the subjects, 29.8% were 28â37 years old, with 69.1% males and 30.9% females. Most of them suffered from paranoid schizophrenia (71.3%). The body mass index (BMI) of 46.8% subjects were normal, 45.74% were overweight, whereas 7.45% were underweight. Male subjects mostly had smaller waist circumference (78%) compared to females who were dominantly above normal (52%). Physical activity levels were mostly sedentary (76%). Single typical APD were dominantly prescribed (46%). Subjects with normal BMI were mostly found among single typical APDs prescribers (53.5%), whereas the majority of atypical APDs users were overweight (61.9%). A total of 63% subjects had been prescribed APDs for 1â5 years, dominated by subjects with normal body mass index (78%). Conclusions: The majority of study subjects (46.8%) were found normal in terms of the body mass index. Male subjects mostly had normal waist circumference (78%) while females have a higher risk with measurement above normal as a more dominant finding (52%). [AMJ.2014;1(1):40â7]Keywords: Nutritional Status, Pscychiatry, SchizophreniaStatus Gizi Pasien Skizofrenia di Departemen Psikiatri Rumah Sakit Dr. Hasan Sadikin BandungLatar Belakang: Saat ini Skizofrenia merupakan suatu penyakit mental dengan komorbiditas yang tinggi akibat perubahan gaya hidup, faktor predisposisi, dan dampak mengonsumsi obat antipsikotik yang membuat penderita kerap mengalami perubahan berat badan. Oleh karena itu, diperlukan deteksi dini perubahan berat badan pada pasien skizofrenia sebagai pertimbangan penyusunan tatalaksana yang komprehensif.Metode: Studi deskriptif potong lintang ini dilakukan untuk mengetahui status gizi pasien skizofrenia di Klinik Rawat Jalan Departemen Psikiatri Sub Bagian Dewasa Rumah Sakit Dr. Hasan Sadikin Bandung. Pengukuran Indeks Massa Tubuh (IMT) dan lingkar pinggang dilakukan pada 94 pasien skizofrenia dewasa. Wawancara mengenai pekerjaan juga dilakukan untuk mengetahui tingkat aktifitas fisik, riwayat pengobatan responden didapatkan melalui rekam medis.Hasil: Dari 94 respondenÂ  (65 pria dan 29 wanita) mayoritas berusia 28â37 tahun (29.8%). Sebanyak 46.8% responden memiliki IMT normal, 45.74% responden adalah overweight, dan 7.45%Â  termasuk dalam kategori underweight. RespondenÂ  pria memiliki ukuran lingkar pinggang yang mayoritas normal (78%), sedangkan wanita sebagian besar memiliki ukuran lingkar pinggang di atas normal (52%). Tingkat aktifitas fisik responden rata-rata tergolong ringan (67%). Kebanyakan responden diberikan obat antipsikotik tipikal tunggal (46%) dan sebanyak 63% telah mengonsumsi obat antipsikotik selama 0â5 tahun. Simpulan:Â  MayoritasÂ Â  respondenÂ Â  memilikiÂ  IMTÂ  yang normal denganÂ  ukuran lingkar pinggang wanita lebih tinggi dibandingkan dengan pria.Kata Kunci: Status Gizi, Psikiatri, Skizofrenia